Mechanosensitive PIEZO2 channels shape coronary artery 28 development - Pampols-Perez, Mireia; Fürst, Carina; Sánchez-Carranza, Oscar; Cano, Elena; García-Contreras, Jonathan Alexis; Mais, Lisa; Luo, Wenhan; Raimundo, Sandra; Lindberg, Eric L.; Taube, Martin; Heuser, Arnd; Sporbert, Anje; et al. (Springer Nature, 2025)
Coronary arteries develop under constant mechanical stress. However, the role of mechanosensitive ion channels in this process remains poorly understood. Here we show that the ion channel PIEZO2, which responds to mechanical stimuli, is expressed in specific coronary endothelial cell populations during a critical phase of coronary vasculature remodeling. These Piezo2+ coronary endothelial cells show distinct transcriptional profiles and have mechanically activated ionic currents. Strikingly, PIEZO2 loss-of-function mouse embryos and mice with human pathogenic variants of PIEZO2 show abnormal coronary vessel development and cardiac left ventricular hyperplasia. We conclude that an optimal balance of PIEZO2 channel function contributes to proper coronary vessel formation, structural integrity and remodeling, and is likely to support normal cardiac function. Our study highlights the importance of mechanical cues in cardiovascular development and suggests that defects in this mechanosensing pathway may contribute to congenital heart conditions.
Keywords: Arterias coronarias; Circulación coronaria; Corazón - Enfermedades; Coronary vasculature; Endothelium; Piezo2; Mechanosensing